PROBLEMS OF INTERPRETATION OF CRUELTY AND VIOLENCE TOWARDS MINOR IN CRIMINAL LAW - Kipāne, Aldona (Administrative and Criminal Justice, 2016)
Violence and cruelty against children is not only problem in Latvia but it is also global problem. There is a special section in Latvian Criminal Law regarding to protection minor against cruel and violence. The article is devoted to the analysis of the corpus delicti of cruel towards and violence against a minor. The author has analysed difference between concepts cruelty treatment towards minor and violence against minor. The author of the paper came to conclusion that necessary condition for proceeding of qualification is scrutiny of all circumstances of crime.